Prawo osobowe na ziemiach polskich wcielonych do Rzeszy Niemieckiej podczas drugiej wojny światowej - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The subject of this article are basic questions within the range of civil law. They concern the general position of a human and legal people in the sphere of this law on Polish territory, which was incorporated into the Third Reich. The position of individuals, the citizens of II RP, under the occupation of the Third Reich in years 1939–1945, is analysed by the author not from the perspective of literal meaning of regulations of general part of Bürgerliches Gesetzbuch (BGB) from 1896, but from the perspective of their specific interpretation, congruent with strategic and ideological purposes of the Nazi regime. In the article, the following issues are touched upon in turn: 1) personal law in terms of classical civil law contra national-socialist regime; 2) racism towards civil rights of a subjective individual; 3) elimination of the Jews from the legal relationships of civil law; 4) difficulties in the sphere of access to certain professions for Polish people and some restrictions upon personal rights; 5) the dependence of possibilities of exercising the private personal right on the consent to denationalization; 6) ban concerning getting married and the right to motherhood and fatherhood; 7) legislation of sterilisation and euthanasia. The formal changes in the legislation which were in force in the Third Reich — except for personal and family law (as well as legal rules connected with it regarding health protection of offspring), and “peasant law” (Bauernrecht) — were not significant, as is proved by the author. The old legal order was reversed in the Third Reich due to its new interpretation: classical concepts and legal institutions were filled with a different content. After the formal extension of BGB to territories incorporated into the Reich, which followed the decree of 25 September 1941 introducing German civil law, these territories became a field of social-political and racial-nationalist experiments, which in fact had a little in common with the German Civil Code’s regulations. A principle of equal access to private subjective rights was respected only in case of German people, i.a. the part which passively gave up to indoctrination. In relation to Jews, racism spoiled in this case the idea and concept of private subjective rights.
Keywords: Bürgerliches Gesetzbuch z 1896 roku; prawa podmiotowe prywatne jednostek; prawa osobistości (Persönlichkeitsrechtes); nierówność wobec prawa; rasizm; prawo rasowe (Rassenrecht); „obcy rasowo”; eugenika; eutanazja; pozycja prawna obywateli polskich pod niemieckim prawem okupacyjnym